Accumulation, detoxification, and toxicity of dibutyl phthalate in the swimming crab. (February 2022) - He, Yimin; Lin, Weichuan; Shi, Ce; Li, Ronghua; Mu, Changkao; Wang, Chunlin; Ye, Yangfang
Abstract: Dibutyl phthalate (DBP) is one of the most commonly used and toxic phthalate esters and has a variety of harmful effects on aquatic animals. However, there is still a lack of knowledge on the accumulation, detoxification, and toxicity of DBP in aquatic animals. In this study, we chose the swimming crab Portunus trituberculatus, an ecologically and economically important species, as the model and investigated the metabolism of DBP and its effects on the detoxification, antioxidation, survival and growth of the crab juveniles to better understand DBP-triggered molecular response over different time courses. As a result, DBP could be accumulated in the swimming crab in a concentration-dependent manner and metabolized to monobutyl phthalate (MBP) and phthalic acid (PA) through de-esterification. DBP exposure induced the different responses of three cytochrome P450 members and antioxidant enzyme genes, enhanced gene transcript and protein levels of glutathione-S-transferase and two heat stress proteins and malondialdehyde accumulation, decreased glutathione level, and inhibited antioxidant enzyme activities. Further, no significant effect of DBP was observed in crab survival, size, and weight but there was molting retardation. Therefore, DBP induced strong detoxification and antioxidative defense mechanisms to overcome detrimental effects of DBP on the swimming crab juveniles despite a molting retardation as a trade-off in fitness costs. The prevalent coexistence of DBP with MBP and PA during the whole exposure period is raising concerns on the combined action and ecological risk to aquatic animals. Graphical abstract: Image 1 Highlights: Dibutyl phthalate (DBP) could be accumulated and metabolized in the swimming crab. The CYP-GST enzymatic system could be involved in the metabolism of DBP. DBP can be a crucial modulator in antioxidant defense systems in the swimming crab. DBP did not affect the survival of swimming crab but retarded its molting.